2012
DOI: 10.1161/strokeaha.111.635045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Socioeconomic Status on Distance Traveled and Care After Stroke

Abstract: Background and Purpose-Vital to maintaining an efficient delivery of services is an understanding of patient travel patterns during an acute ischemic stroke. Socioeconomic status may influence access to stroke care, including transportation and admission to different facility types. Key Words: accessibility Ⅲ health services Ⅲ stroke I n the past 2 decades, there has been an unprecedented increase in population age, bringing an increased burden of stroke and the need for efficient high-quality health care deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Previous studies demonstrated decisions for treatment at the closest or a more distant medical center are determined by a variety of factors: desire for treatment at centers with high surgeon and hospital volumes, option to avoid centers with perceived quality care differences, motivation for aggressive treatment, and travel distance considerations. 4,17,18 Our study compliments these by asserting that whatever the patients' motivation to travel further for their care, the distance they travel will not increase their hospital costs or length of stay.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies demonstrated decisions for treatment at the closest or a more distant medical center are determined by a variety of factors: desire for treatment at centers with high surgeon and hospital volumes, option to avoid centers with perceived quality care differences, motivation for aggressive treatment, and travel distance considerations. 4,17,18 Our study compliments these by asserting that whatever the patients' motivation to travel further for their care, the distance they travel will not increase their hospital costs or length of stay.…”
Section: Discussionsupporting
confidence: 53%
“…43 Therefore, the number of stroke centers in Iran should be increased and adjusted to the size and population of each area to minimize the delay in patients' arrival time. 44 The clinical efficacy and safety of lower dosage of rtPA are approved in Japan (.6 mg/kg body weight; maximum 60 mg). 13 However, compared with the criteria recommended in the American, European, and Japanese guidelines for rtPA (Alteplase) administration, 1,13,45 we used a different selection criteria for the present study, which was based on a general consensus between the members of the stroke center with respect to the socioeconomic infrastructural limitations and previous experience.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, data from the US and Canada suggest that socioeconomic status does not have a significant effect on hospital choice, so increased geographic accessibility should benefit all people. 40, 41 Improving access in suburban and rural areas may pose challenging. Although there are more than 50 million Americans living in non-urban areas, low population density and/or limited physician/hospital resources may make it difficult to provide PSC access to all of these people.…”
Section: Discussionmentioning
confidence: 99%